Evaluation and Assessment of Fluoride in Drinking Water Wells Damavand Villages Zoning in GIS According to DMF Index - Kave Kheirkhah Rahimabad; Amir Hessam Hasani; Reza Saeedi; Mir Masoud Kheirkhah Zarkesh; Mojtaba Sayadi (Muhandisī-i Bihdāsht-i Muḥīṭ, 2016)
Background:Fluoride is one the vital anions and the drinking water is the main source of preparing it for the human body. Nonetheless, the aim of this paper is to investigate the Fluoride rate in water supplying wells by using GIS environment according to decay, missing or filled (DMF) index.